Gender differences in the prevalence of Tuberculous Lymphadenitis at the State of Penang, Malaysia: Findings from a cross-sectional study - Ridhwan Abdullah; Mohamed Azmi Hassali; Abdul Razak Muttalif; Amer Hayat Khan*, Syed Azhar Syed Sulaiman (Archives of Global Professionals, 2010)
Objective: To evaluate the prevalence of tuberculous lymphadenitis on the basis of gender in the northern state of Malaysia.Materials and Methods: Current study was divided into two phases (Retrospective and Prospective), which was conducted at the Department of Chest in General Hospital Penang. Patient records were reviewed retrospectively, and prospectively to identify patients with confirmed diagnosis of tuberculous lymphadenitis under the clinical signs and symptoms, and laboratory tests from January 2006 to December 2008. Data were analyzed using SPSS version 16.Results: One hundred and nine patients (7.2%) with confirmed tuberculosis lymphadenitis cases were found,among 1516 of total TB cases. The mean age of the patients was 36.4±12.87. The male to female ratio was 1.4:1. Ethnically,45 (41.3%) were Malay followed by Chinese 37 (33.9%).Among the risk factors were, HIV and diabetes mellitus, 17(15.6%) and 11(10.0%) respectively. Cough and fever were the most common symptoms in both gender groups. Night sweat,cough, shortness of breathing were observed more in male than female, while swelling of lymph nodes, loss of appetite,loss of weight, haemoptysis, and chest pain were higher in female. In the majority, 90 (82.5%) positive results were obtained by fine needle aspiration (FNA) cytology. Overall sixtytwo (56.9%) patients were successfully treated, 5 (4.6%)patients died during the treatment, while male were higher in successfully treated (59.7%).Conclusion: Incidence of TB Lymphadenitis was found higher among Malay men. Diabetes mellitus and HIV are the most commonly reported risk factors and co-morbidities playing an important role in treatment success while, 12 months treatment were observed among 10 (9.2%) of cases. Treatment successful rate were higher in male as compare to female.